2021
DOI: 10.3390/fractalfract5040171
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Walks in Hilbert Space of Lévy Matrices: Recurrences and Revivals

Abstract: The quantum evolution of wave functions controlled by the spectrum of Lévy random matrices is considered. An analytical treatment of quantum recurrences and revivals in the Hilbert space is performed in the framework of a theory of almost periodic functions. It is shown that the statistics of quantum recurrences in the Hilbert space of quantum systems is sensitive to the statistics of the corresponding quantum spectrum. In particular, it is shown that both the Poisson energy level statistics and the Brody dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Iomin, in his paper "Quantum Walks in Hilbert Space of Lévy Matrices: Recurrences and Revivals" [3], considered the quantum evolution of wave functions, which is controlled by the spectrum of Lévy random matrices. By the analytical treatment of quantum recurrences and revivals in the Hilbert space, the author showed that, for chaotic systems with a uniform mixing property, the distribution of the return probability is exponential, while in systems with nonuniform mixing, the distribution of the return probability is algebraic in large recurrence times.…”
mentioning
confidence: 99%
“…Iomin, in his paper "Quantum Walks in Hilbert Space of Lévy Matrices: Recurrences and Revivals" [3], considered the quantum evolution of wave functions, which is controlled by the spectrum of Lévy random matrices. By the analytical treatment of quantum recurrences and revivals in the Hilbert space, the author showed that, for chaotic systems with a uniform mixing property, the distribution of the return probability is exponential, while in systems with nonuniform mixing, the distribution of the return probability is algebraic in large recurrence times.…”
mentioning
confidence: 99%